Elevation of Fatty Acid Biosynthesis Metabolism Contributes to Zhongshengmycin Resistance in Xanthomonas oryzae - Qiaoxing Wang; Meiyun Lin; Peihua Shen; Yi Guan (MDPI AG, 2021)
Xanthomonas oryzae severely impacts the yield and quality of rice. Antibiotics are the most common control measure for this pathogen; however, the overuse of antibiotics in past decades has caused bacterial resistance to these antibiotics. The agricultural context is of particular importance as antibiotic-resistant bacteria are prevalent, but the resistance mechanism largely remains unexplored. Herein, using gas chromatography-mass spectrometry (GC-MS), we demonstrated that zhongshengmycin-resistant X. oryzae (Xoo-Rzs) and zhongshengmycin-sensitive X. oryzae (Xoo-S) have distinct metabolic profiles. We found that the resistance to zhongshengmycin (ZS) in X. oryzae is related to increased fatty acid biosynthesis. This was demonstrated by measuring the Acetyl-CoA carboxylase (ACC) activity, the expression levels of enzyme genes involved in the fatty acid biosynthesis and degradation pathways, and adding exogenous materials, i.e., triclosan and fatty acids. Our work provides a basis for the subsequent control of the production of antibiotic-resistant strains of X. oryzae and the development of coping strategies.